1995
DOI: 10.2172/102150
|View full text |Cite
|
Sign up to set email alerts
|

Weld-overlay iron-aluminide coatings for use in high-temperature oxidizing/sulfidizing environments

Abstract: The development of iron-aluminide weld overlay coatings for high-temperature oxidation and sulfidation resistance critically depends on the determination of the aluminum concentration range for which good corrosion behavior and weldability coexist. This study demonstrated that a sound weld overlay composition with about 30 at.% A1 has relatively low corrosion rates in a highly aggressive oxidizing/sulfidizing (H2S -H2 -H20 -Ar) environment at 800°C. Its corrosion resistance was superior to alloys with composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
0
6
0
Order By: Relevance
“…This concept was studied and modeled by Quadakkers et al (1994a and1994b) and recently reviewed by Tortorelli and Natesan (1998). The time frame for protection has been found to be a fimction of the total amount of aluminum available for reaction (at the surface and in reserve) and the rate at which it is consumed.…”
Section: Inhibition Stagementioning
confidence: 99%
See 1 more Smart Citation
“…This concept was studied and modeled by Quadakkers et al (1994a and1994b) and recently reviewed by Tortorelli and Natesan (1998). The time frame for protection has been found to be a fimction of the total amount of aluminum available for reaction (at the surface and in reserve) and the rate at which it is consumed.…”
Section: Inhibition Stagementioning
confidence: 99%
“…Intermetallic iron aluminide alloys based on the ordered structures of F@l and FeAl show excellent resistance to oxidation and sulfidation in highly aggressive environments (McKamey, 1991;DeVan, 1993aDeVan, , 1993bTortorelli, 1995Tortorelli, , 1994% 1994b. This outstanding resistance has been attributed to the formation of a dense, adherent surface scale of aluminum oxide (A1203) which is stable under a wide range of environments.…”
Section: Introductionmentioning
confidence: 99%
“…Although weld overlays were the coatings of interest, cast alloys were used because it was shown previously that the hightemperature corrosion behavior of weld claddings could be explained by using cast alloys of equivalent composition. 13 It has been reported since that the corrosion behavior between weld overlays and cast alloys are similar due to the lack of microsegregation within the welds and both having coarse-grained microstructures. 14 Binary Fe-Al alloys, ternary Fe-Al-Cr alloys, and quaternary Fe-Al-Cr-Ti alloys that were used for this study are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Bamba [13] and Guo [14] reported that the addition of Cr to Fe-Si alloy can induce the formation of SiO2 layer in pure oxidizing atmosphere. Second, we also could decrease the grain size of the alloy to improve the outward diffusion of the Cr and Si to achieve the selective oxidation of Si and form the protective scale [11,12]. In our previous study, the Fe-Si alloy exhibited poor corrosion resistance in the H2-CO2-H2S at 700 o C [3], which is not acceptable.…”
Section: Introductionmentioning
confidence: 99%
“…Dudziak et al [11] reported that multilayer CrAlYN/CrN coatings could induce a protective layer locally on Ti-45Al-8Nb in H2/H2S/H2O mixture. Besides, Nano-or micro-coating is reported to be able to improve the oxidation/sulphidation resistance of the alloy [12].…”
Section: Introductionmentioning
confidence: 99%